Free vibration analysis of cracked Kirchhoff-Love plate using the extended radial point interpolation method - Lo, Vay Siu; Nguyen, Nha Thanh; Nguyen, Minh Ngoc; Truong, Thien Tich (Vietnam Journal of Science and Technology, 2021)
The Kirchhoff-Love plate theory is appropriate for analysing thin plate structures. In a simple form, only one degree of freedom (per node) is needed to describe the behaviour of the plate, thus saving the computational cost. Besides, the analysis of cracked structures is important because it is related to the lifetime of the structures. Therefore, this paper uses the extended radial point interpolation method (XRPIM) to investigate the free vibration of the Kirchhoff-Love plate. The XRPIM is based on RPIM so the requirement for calculating the second-order derivative in Kirchhoff-Love theory is easily done. The numerical results from this study are compared with other researchers to verify the accuracy of the method.